Resident memory T cells form during persistent antigen exposure leading to allograft rejection - Abou-Daya, Khodor I. (Sci Immunol, 2021)
Tissue resident memory T cells (T(RM)) contained at sites of previous infection provide local protection against re-infection. Whether they form and function in organ transplants where cognate antigen persists is unclear. This is a key question in transplantation as T cells are detected long-term in allografts, but it is not known whether they are exhausted or are functional memory T cells. Using a mouse model of kidney transplantation, we showed that antigen-specific and polyclonal effector T cells differentiated in the graft into T(RM) and subsequently caused allograft rejection. T(RM) identity was established by surface phenotype, transcriptional profile, and inability to recirculate in parabiosis and re-transplantation experiments. Graft T(RM) proliferated locally, produced IFNγ upon re-stimulation, and their in vivo depletion attenuated rejection. Importantly, the vast majority of antigen-specific and polyclonal T(RM) lacked phenotypic and transcriptional exhaustion markers. Single cell analysis of graft T cells early and late after transplantation identified a transcriptional program associated with transition to the tissue resident state that could serve as a platform for the discovery of therapeutic targets. Thus, recipient effector T cells differentiate into functional graft T(RM) that maintain rejection locally. Targeting these T(RM) could improve renal transplant outcomes.